Metal-Free Aminohalogenation of Quinones With Alkylamines and NXS at Room Temperature - Li, Jia; Li, Yu-An; Wu, Ge; Zhang, Xu (Frontiers in Chemistry, 2022)
A simple and practical strategy for intermolecular aminohalogenation of quinone with alkyl amines and NXS was developed, in which haloamines generated in situ were employed as bifunctional reagents. The reaction system is reliable, efficient and wide in substrate range, which is suitable for the two-fold aminochlorination of 1, 4-benzoquinones, large-scale reaction and late-stage modification of pharmaceuticals.